2014
DOI: 10.22226/2410-3535-2014-1-52-54
|View full text |Cite
|
Sign up to set email alerts
|

The increase of impact strength of ultrafine grained nickel after ultrasonic treatment

Abstract: Impact strength tests of nickel samples exposed to equal-channel angular pressing (ECAP) were carried out. The influence of annealing and ultrasonic treatment with stress amplitudes of 20, 50 and 100 MPa on the impact fracture of ultrafine grained nickel processed by ECAP was shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…В работах [13,14] была иссле-дована зависимость механических свойств никеля, под-вергнутого равноканальному угловому прессованию, от амплитуды ультразвука. Было показано, что эта за-висимость является немонотонной, и существует опти-мальное значение амплитуды ультразвука, при котором и предел прочности, и удлинение до разрушения дости-гают максимума.…”
Section: Introductionunclassified
“…В работах [13,14] была иссле-дована зависимость механических свойств никеля, под-вергнутого равноканальному угловому прессованию, от амплитуды ультразвука. Было показано, что эта за-висимость является немонотонной, и существует опти-мальное значение амплитуды ультразвука, при котором и предел прочности, и удлинение до разрушения дости-гают максимума.…”
Section: Introductionunclassified
“…Later studies of HPT-processed Ni have shown that the effect of UST is not monotonous: first an increase of the GB energy, rms strains, microhardness occurs with an increase of the UST amplitude, then all these characteristics decrease indicating on the GB relaxation [24,25]. Studies using ECAP-processed Ni revealed an uncommon effect of UST on mechanical properties: at stress amplitudes 50 ÷ 90 MPa it resulted in a simultaneous enhancement of both the elongation to failure and ultimate strength at room temperature tensile tests [22].…”
Section: Relaxation Of Nonequilibrium Grain Boundaries Induced By Cycmentioning
confidence: 99%
“…In [22] the following qualitative comparison between the effects of annealing and UST was proposed. The thermodynamic state of an as-prepared UFG metal can be considered as a point in the phase space.…”
Section: Relaxation Of Nonequilibrium Grain Boundaries Induced By Cycmentioning
confidence: 99%
“…UST of equal-channel angular pressing (ECAP) processed nickel also resulted in a simultaneous increase of ductility, strength and impact toughness [26,27].…”
Section: Introductionmentioning
confidence: 99%